Single nucleotide polymorphisms as next generation markers for high throughput screening for crown rust resistance in oat - Chen, Gang; Chong, James; Gray, Mark; Prashar, Suvira; Procunier, Douglas (MTT, 2004)
Single nucleotide polymorphisms (SNPs) have rapidly gained popularity as markers of choice because of availability of automated high throughput technologies to genotype them. Direct sequencing of genes and their comparative alignment between genotypes is one approach to SNP discovery. Existing RFLP markers can be used as a source of these genes. The objectives of this study were to discover SNPs in oat using existing RFLPs associated with crown rust resistance, and to determine if such association was retained in the RFLP-derived SNPs so these could be used as markers in genetic studies. Ten RFLP markers used in this study were sequenced and oligonucleotide primers were designed. One marker (cdo309) was mapped near a cluster containing the crown rust resistance gene Pc68. Putative SNP sites between resistant and susceptible plants were identified by direct sequencing and sequence alignment of the PCR products. The Single Base Extension (SBE) assay was used to validate SNPs, using an Applied Biosystems ABI 3100 Genetic Analyzer for capillary electrophoresis of SBE products. Linkage of SNPs to Pc68 was determined in two populations segregating for this gene. Ten SNPs between resistant and susceptible plants were validated by SBE. Two, derived from cdo309, were associated with Pc68. Linkage to Pc68 (3.9- 4.4cM) was confirmed in two populations. Results showed that SNPs in oat can be derived from RFLPs and applied as markers to genetic studies. The automated ABI 3100 system provided accurate analysis of SNP sites. The throughput is 1,152 samples per 24 hr, with capability to multiplex to 10 SNP sites. Estimated costs are $0.40 per SNP site. The Invader® Operating System requires no prior PCR amplification of genomic DNA to detect SNPs, is quantitative and can detect heterozygosity, making SNPs even more attractive as the next generation markers for high throughput screening.
Keywords: Ka; SNP markers; high-throughput; single base extension